Product Quality, Price Perception, and Customer Loyalty: The Mediating Role of Customer Satisfaction among Herbalife Consumers in Indonesia - Alfi Rachmatunnisa; Faizal Fardhani Sigarlaki (Jurnal Investasi Islam, 2026)
This study examines the effects of product quality and price on customer loyalty through the mediating role of customer satisfaction among Herbalife customers in Cianjur City, Indonesia. The research is grounded in the Stimulus-Organism-Response (S-O-R) theory, which explains how external marketing stimuli influence internal psychological states and subsequently shape behavioral responses. A quantitative survey method was employed using purposive sampling, involving 70 Herbalife customers who had purchased and consumed Herbalife products more than once. Data were analyzed using multiple linear regression and Sobel mediation tests with IBM SPSS Statistics 26. The findings reveal that product quality (β = 0.380; p < 0.001) and price (β = 0.326; p < 0.001) have positive and significant effects on customer satisfaction. Customer satisfaction also exerts a positive and significant effect on customer loyalty (β = 0.786; p < 0.001). However, product quality demonstrates a significant negative direct effect on customer loyalty after customer satisfaction is introduced into the model, indicating competitive (inconsistent) mediation, while price does not directly influence customer loyalty. The Sobel test confirms that customer satisfaction significantly mediates the relationships between product quality and customer loyalty (Z = 2.98) and between price and customer loyalty (Z = 2.85). These findings extend the application of S-O-R theory within the health nutrition industry by demonstrating that customer loyalty is primarily established through customer satisfaction rather than through product quality or price alone. Practically, Herbalife should prioritize enhancing customer satisfaction by maintaining superior product quality, ensuring value-based pricing, and strengthening customer education and relationship marketing to foster long-term customer loyalty.